ANALISIS PENGARUH DAU, DAK, DAN DBH TERHADAP IPM DI KABUPATEN/KOTA EKS KARESIDENAN KEDU TAHUN 2012-2016 - Puji Lestari; Sudati Nur Sarfiah; Panji Kusuma Prasetyanto (DINAMIC : Directory Journal of Economic, 2019)
This study aims to analyze the effect of general allocation funds, special allocation funds, and profit sharing funds on the human development index in the former Kedu Residency districts / cities in 2012-2016. Human development index as the dependent variable, while general allocation funds, special allocation funds, and profit sharing funds as independent variables. This research uses panel data analysis with the approach of Fixed Effect Model (FEM). The results show that human development index is able to be explained by general allocation funds, special allocation funds, and simultaneous revenue-sharing funds, then the human development index is significantly influenced by general allocation funds, special allocation funds, and profit sharing funds simultaneously. But partially shows that general allocation funds have a positive and significant effect on the human development index, while special allocation funds and profit sharing funds have a positive and not significant effect on the human development index. Keywords: general allocation funds, special allocation funds, profit sharing funds, human development index.